The Form of Culture in the Blarak-Blarak Sempal Game: A Study of Literary Anthropology - Azis, Muhammad Malik; Wulandari, Yosi (Journal of Language and Literature Studies, 2024)
This study aims to describe the form of Javanese culture and cultural elements in the traditional game of Blarak-Blarak Sempal through a literary anthropological approach. Using descriptive qualitative methods, this study reveals cultural symbols such as coconut fiber that symbolizes attachment to nature, and pingsut that reflects deliberation and honesty. The poems and songs that accompany the game also describe important elements in the language and art system of Javanese society. These findings make an important contribution to enriching the understanding of the social and cultural values contained in traditional games, while highlighting the role of these games as a medium of cultural and moral education. The implications of the results of this study support local cultural preservation policies, especially in the field of education, by integrating traditional games as a tool to teach cultural values to the younger generation. In addition, this study opens up opportunities for further research related to the role of other traditional games in character formation and strengthening cultural identity among the community. Thus, traditional games such as Blarak-Blarak Sempal have great potential to be preserved and used as a means of learning noble values in community life.